2001
DOI: 10.33584/jnzg.2001.63.2408
|View full text |Cite
|
Sign up to set email alerts
|

Perennial ryegrass cultivars: herbage yield in multi-site plot trials

Abstract: Perennial ryegrass (Lolium perenne) cultivars adapted to New Zealand conditions are bred by several scientifically equipped New Zealand interests. New cultivars are evaluated in a network of trials organised by the New Zealand Plant Breeding and Research Association. This paper presents data from 17 trials completed throughout New Zealand since 1991. Data were analysed for each trial and then in a multi-site analysis enabling comparison of estimated cultivar means, over all New Zealand trials, North Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 7 publications
3
35
0
Order By: Relevance
“…There were significant differences among cultivars in total annual and seasonal DM yield in all five seasons analysed (Table 2), with yields similar to those in previous ryegrass cultivar comparison work (Easton et al 2001). These differences could be expected to translate to sizeable differences in profitability.…”
Section: Dm Yieldsupporting
confidence: 78%
See 1 more Smart Citation
“…There were significant differences among cultivars in total annual and seasonal DM yield in all five seasons analysed (Table 2), with yields similar to those in previous ryegrass cultivar comparison work (Easton et al 2001). These differences could be expected to translate to sizeable differences in profitability.…”
Section: Dm Yieldsupporting
confidence: 78%
“…Genetic improvement of pasture plants has been pursued for over 85 years (Wratt & Smith 1983), with documented gains in dry matter (DM) production, disease resistance and forage quality (Corkill 1949;Kerr 1987;Easton et al 1989;Easton et al 1997;Woodfield 1999;Easton et al 2001). Genetic gains averaging around 0.5% per year for total annual DM yield (Lee et al 2012) have been demonstrated through small plot trials (Kerr 1987;Pennell et al 1990;Easton et al 2001;Hume et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Data from an independent cultivar yield trial showed that the rank correlation between cultivars for estimates of DM yield collected from a single regrowth period compared with the 2‐year trial mean was statistically significant for all periods, except during the flowering period, and ranged from 0·61 to 0·80 ( P < 0·01 to P < 0·001; C. Matthew, unpublished data). Additionally, herbage mass for the cultivars in the current trial correlated ( r = 0·86, P = 0·0028) with mean total annual herbage accumulation measured in National Forage Variety (NFV) yield trials (managed by the New Zealand Plant Breeders Research Association and conducted as described by Easton et al ., ) in the northern North Island. These NFV trial data are used to generate cultivar performance values in the DairyNZ Forage Value Index (FVI; Chapman et al ., ), which includes six of the eight cultivars used here.…”
Section: Discussionmentioning
confidence: 99%
“…There is little experimental evidence that modern ryegrass cultivars as a group are less persistent than older cultivars (Easton, Stewart, & Kerr, 2011). When compared under the same conditions, management and endophyte status, new cultivars have maintained their production and sward composition at least as well as older cultivars (Crush, Woodward, Eerens, & MacDonald, 2006; Easton et al, 2001). There is some evidence that higher‐producing, more recent cultivars may be more prone to population collapse under severe defoliation in extremely dry or impoverished conditions (Hazard, Barker, & Easton, 2001).…”
Section: Introductionmentioning
confidence: 99%